Conflicts of decision-making processes between Clean Development Mechanism and project financing. Issue 8 (16th November 2016) - Ogino, Kaoru
ABSTRACT: Clean Development Mechanism (CDM) projects are believed to be financially unviable without additional revenues from CDM in the form of saleable certified emission credits; this is an important premise to be verified in the CDM approval process. However, in financing a CDM project, it is crucial for financiers and investors to ensure that the project is viable without CDM revenues. Thus, there are clear conflicts in the processes and priorities between the CDM approval in theory, and financing and investment decisions in practice. Considering the post-CDM frameworks, this article uses a case study of Bhutan's Dagachhu hydropower project, the world's first cross-border CDM project, to suggest practical lessons learnt.